Multi-technique structural characterization of glass foams with complex pore structures obtained through phase separation. (28th April 2021) - de Oliveira, Cristine S.; Kohns, Richard; Meyerhöfer, Felix; Carstens, Simon; Enke, Dirk; Wehrspohn, Ralf B.; Martins de Souza e Silva, Juliana
Abstract : Typical pore characterization techniques combined with computed tomography provided a complete description of the multimodal porous architecture of novel glass foams synthesised via foaming process followed by phase-separation and selective leaching. Abstract : Glass foams (GF) are materials with a porous framework characterized by pore sizes spanning different orders of magnitude. In this study, we report for the first time the synthesis and characterization of GF with cavities ranging from macro- to mesopore size obtained via the combination of a foaming process with phase separation and followed by selective leaching. A combination of techniques, namely N2 sorption, Hg intrusion, scanning electron microscopy, and high-resolution X-ray computed tomography, enabled us to characterize the pores within different size ranges, showing that the GF produced have a complex multimodal pore structure. Computed tomography provided a visual and detailed quantitative description of the pores of hundreds of nanometers to several hundred micrometers and confirmed the presence of residues of the foaming agents still present in the GF walls. We present a comparison of the techniques used for characterizing the produced foams with a discussion of their advantages and limitations. Our results reveal that our multi-technique approach to characterize pores is valuable for developing novel porous materials with features in the nanometric range since it enables building a complete overview of the porous architecture in different size ranges, as no single technique alone would provide.